Study on Mechanical Properties and Damage Evolution Law of Secondary Destruction Induced by Simultaneous Unloading after the Peak of the Curve of Sandstone - Xiao Fukun; Liu Gang; Cheng Qianlong (Shock and Vibration)
The research adopts the French ROCK600-50 three-axis experiment instrument and SH-II system to evaluate the acoustic emission (AE) peak of the rear axle of yellow sandstone by carrying out the confining pressure synchronous unloading experiment, and evolution of mechanical properties and characteristics of energy transformation and damage of a yellow sandstone, which is a two-damage process, the results of which have shown the following: (1) there are two damages appearing when the confining pressure is 5 MPa, 10 MPa, and 20 MPa. In contrast, these two damages do not appear when the confining pressure is 30 MPa and 40 MPa. The fracture degree and crack number of the two fractures are larger than those without two damages. (2) A failure stress release rate showed an obvious “√” trend. With the increase of confining pressure, the stress release rate of the two failures is increasing. (3) By keeping the strain of the body constant, it is determined to be the first time to destroy the warning. The two failures of rock are predicted by the inflection point of the axial strain slope. No two failures occurred, and the strain unloading process showed two characteristics. (4) Meanwhile, with the increase of confining pressure, the energy released from the peak decreases first and then increases; the law of releasing energy from one failure and two destructions is the opposite. No damage occurred two times. As the confining pressure increases, there is a continuous decrease of the energy released from the peak. As the confining pressure increases, the release rate of the primary energy decreases at first and then increases, and the rate of energy released two times is increasing. The plasticity coefficient shows the trend of increasing first and then decreasing. (5) The damage degree of the second rupture is greater than the first rupture.